SOME OBSERVATIONS ON THE SHOALING BEHAVIOUR OF THE OIL-SARDINE SARDINELLA LONGICEPS VAL - Balan, V (Indian Journal of Fisheries, 2011)
THE importance of the knowledge of the behaviour of fish in their naturalenvironment which enables their easier location, the devising of better gearand techniques of capture has long been realized by fishery workers. Studiesof that nature already conducted have proved to be of considerable interestand value in the case of various fishes such as the Australian pilchardSardinops neopilchardus (Blackburn, 1941; Blackburn and Tubb, 1950), theCalifornia sardine, Sardinops ccerulea (Anon, 1952), the Japanese sardine,Sardinops melanosticta (Nomura, 1958), the " lemuru", Sardinella allecia(Soerjodinoto, 1958), the Atlantic salmon (Keenleyside, 1958), the tunas,Katsuwonus pelamis (Strasburg and Yuen, 1958), Neothunnus macropterusand Euthynnus yaito (Tester ef al., 1955), thelajang, Decapterus spp. (Soemarto,1958), the cichUd, Tilapia esculenta, the cat fish, Clarias (Beauchamp, 1958),and the minnow, Phoxinus phoxinus (Jones, 1958). Kesteven (1960) in an exhaustivereview has lucidly dealt with almost all aspects of behaviour of fishes.No attempts have hitherto been made towards studies on the shoaUng behaviourof fishes of Indian waters. In view of the importance of the fishery of oilsardineSardinella longiceps on the south-west coast of India, it was thoughtdesirable to investigate the shoaling behaviour of this species.